Plant Taxa Used in the Treatment of Diabetes in Van Province, Turkey - Abdullah Dalar (International Journal of Secondary Metabolite)
Despite the richness of local flora and medicinal plant utilization, there is no any report on documentation of antidiabetic botanicals used in Van province. Therefore, the present study aimed to record accumulation of the traditional antidiabetic medicinal plants of Van province in order to preserve the valuable local medicines knowledge, which has been threatened by urbanization. Antidiabetic folk medicines were determined via field surveys conducted in 1065 settlements during the period of 2014-2017 through medicinal plants questionnaire and structured face-to-face interviews (600 informants) with local people who are well known in the province for their long practice in traditional medicine. 69 plant taxa (35 species with undocumented antidiabetic medicinal use in scientific literature for Turkey) including five endemic and one rare to Turkey belong to 16 families (principally Asteraceae and Lamiaceae) were recorded for their traditional antidiabetic use. 52 different vernacular names were detected which were mainly indicate morphological characteristics. Infusion prepared from leaf and flower organs were found as the most common preparation method of local medicines in the province. Use value analysis showed that Rheum ribes, Urtica dioica, Scutelleria orientalis subsp. pichleri, Diplotenia cachrydifolia, Teucrium polium, Rosa canina, Campanula glomerata subsp. hispida, Rumex scutatus, Helichrysum plicatum subsp. plicatum and Tanacetum balsamita subsp. balsamita might serve promising pharmaceutical agents for diabetes treatment.